Composition, Structure And Diversity of The Vegetation of The Manda National Park (MNP) in The Moyen-Chari Province of Chad - Esaie Waya; Ibrahima Adamou; Tchoua Paul; Maïgari Pale (European Scientific Journal, ESJ, 2022)
The present work was initiated in order to evaluate the composition, structure and diversity of the flora of the Manda National Park (MNP) to contribute to its sustainable management. The survey area is a square plot of 1m x 1m and a semi plot of 10m x 10m respectively for grassy savannah and shrub savannah and a rectangular plot of 50m x 20m for woodland and tree savannah. The diameter at breast height and total height of all woody individuals were measured. The floristic inventory resulted in a total of 12885 individuals belonging to 102 species, 81 genera and 34 families. The tree savannah (78 species, 59 genera and 26 families) and woodland (65 species, 54 genera and 24 families) are richer in taxonomic groups than the shrub savannah (38 species, 32 genera and 16 families) and the grassy savannah (19 species, 18 genera and 8 families) The average density of the park and its Shannon index are respectively 1956 ind/ha and 2.82 bits. For these plant formations, their density and Shannon index are highest in the tree savannah (3507 ind/ha and 3.11 bits) and lowest in the shrub savannah (1133 ind/ha and 2.03 bits). The Piélou index for each of the plant formations is low (0.19 to 0.25), indicating a poor equi- distribution of individuals between the different species for the plant formations. In the woodland, the diametrical and vertical distributions are bell-shaped and skewed to the right, centered on young individuals. In contrast, in the Tree and Shrub Savannahs the distributions are in the shape of an inverted "J", characteristic of a formation dominated by juvenile individuals. These results lead to the conclusion that the Manda Park has a good species diversity and is under anthropic pressure due to the destruction of its vegetation cover.